1998
DOI: 10.1111/j.1600-0420.1998.tb00866.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of class I and class II HLA antigens in primary open angle glaucoma (POAG)

Abstract: Summary Several clinical and epidemiological studies have shown the role of genetic factors in the pathogenesis of primary open angle glaucoma (POAG). In this study, 30 patients affected by this disease were tissue‐typed for HLA Class I and Class II antigens. The results pointed up an increased incidence of some antigens and, particularly, a statistically significant association with DQ1 and DR11 alleles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
(13 reference statements)
0
3
0
1
Order By: Relevance
“…PSS has some clinical features of glaucoma and uveitis, such as the elevated intraocular pressure (IOP) and keratic precipitates (KPs). Human leukocyte antigens (HLA) class I and class II molecule were demonstrated to be significantly associated with uveitis and glaucoma [ 14 26 ]. Many kinds of uveitis including anterior uveitis, multiple sclerosis-associated intermediate uveitis, birdshot chorioretinitis and sympathetic ophthalmia have been associated with class I HLA [ 14 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PSS has some clinical features of glaucoma and uveitis, such as the elevated intraocular pressure (IOP) and keratic precipitates (KPs). Human leukocyte antigens (HLA) class I and class II molecule were demonstrated to be significantly associated with uveitis and glaucoma [ 14 26 ]. Many kinds of uveitis including anterior uveitis, multiple sclerosis-associated intermediate uveitis, birdshot chorioretinitis and sympathetic ophthalmia have been associated with class I HLA [ 14 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…HLA-DRB1*0407~DQB1*0302 haplotype have been significantly associated with POAG in Mexicans [ 25 ]. DR11 and DQ1 alleles have been reported to be significantly associated with POAG in an Italian population [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…43,44 Çeşitli HLA gen ilişkileri de öne sürülmüştür. 45 Primer açık açılı glokomdan sorumlu olduğu düşünülen önemli bir gen de 10p14 lokusundaki OPTN genidir. 46 Bu gen optineurin ("optic neuropathy inducing") proteinini kodlar.…”
Section: B) Glokomunclassified
“…Other studies have identified class II HLA antigens such as HLA-DR3 in a mexican family (6) and HLA DQ I and HLA DR II in Italians (7) . The results of a study conducted in Brazil (8) has suggested a possible association of POAG with the HLA system.…”
Section: Introductionmentioning
confidence: 99%